Financial inclusion and digital banking in rural India: A Review Based study - Ramesh Kumar (AG Volumes, 2025)
The digital banking revolution in India has revolutionized the delivery and accessibility of financial services, with platforms such as mobile banking, Aadhaar-enabled services, and the Unified Payments Interface (UPI) filling in the previous gaps in inclusion. The Indian banking industry’s digital revolution has opened up new avenues for financial inclusion, especially in rural regions. This review examines financial inclusion and digital banking in rural India, highlighting their growing importance in promoting economic empowerment and inclusive development. It explores key challenges such as low financial literacy, digital divide, gender disparities, inadequate infrastructure, and trust issues, along with recent advancements and trends in digital payment adoption. Government initiatives like PMJDY, Digital India, and BharatNet have strengthened connectivity, enabling wider use of digital platforms. Despite persistent barriers, digital banking offers significant benefits, including convenience, reduced transaction costs, and improved access to formal financial services. A holistic, collaborative approach is essential to maximize its impact on rural financial inclusion.